Self-enforcing international environmental agreements: Adaptation and complementarity - Santiago J. Rubio (Fondazione Eni Enrico Mattei (FEEM), 2018)
This paper studies the impact of adaptation on the stability of an international emission agreement. To address this issue we solve a three-stage coalition formation game where in the first stage countries decide whether or not to sign the agreement. Then, in the second stage, signatories (playing together) and non-signatories (playing individually) select their levels of emissions. Finally, in the third stage, each country decides on its level of adaptation non co-operatively. We solve this game for two models. For both, it is assumed that damages are linear with respect to emissions which guarantee that emissions are strategic complements in the second stage of the game. However, for the first model adaptation reduces the marginal damages of emissions in a multiplicative way whereas for the second model the reduction occurs in an additive way. Our analysis shows that the models yield different predictions in terms of participation. In the first case, we find that the larger the gains of full cooperation, the larger the cooperation. However, in the second case, the unique stable agreement we find consists of three countries regardless of the gains of full cooperation. These results suggest that complementarity can play in favor of cooperation but that it is not a sufficient condition to obtain more participation in an emission agreement. Finally, we would like to point out that our research indicates that the way adaptation reduces damages plays a critical role over the outcome of the coalition formation game.
Keywords: D62; F53; H41; Q54; 330; International Environmental Agreements; Mitigation-Adaptation Game; Strategic Complements